2015
DOI: 10.1186/s12879-015-1270-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients on second line antiretroviral therapy under programmatic condition in India

Abstract: BackgroundThe National AIDS Control Organization of India has been providing free second line antiretroviral therapy (ART) since 2008. This observational study reports the survival and virologic suppression of patients on second-line ART under programmatic condition and type of mutations acquired by those failing therapy.Methods170 patients initiated on second-line therapy between 2008 and 2012 were followed up till 2013. Viral Load (VL) was repeated at 6 months for all patients and at 12 months for those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 26 publications
16
31
1
Order By: Relevance
“…The failure rate and overall outcomes of this patient cohort are better than in other studies from similar resource-limited settings [2,5,7,8,13]. A multi-centric study with follow-up duration of three years showed that the probability of survival at one year was 0.86 and at two years it was 0.77 [8].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The failure rate and overall outcomes of this patient cohort are better than in other studies from similar resource-limited settings [2,5,7,8,13]. A multi-centric study with follow-up duration of three years showed that the probability of survival at one year was 0.86 and at two years it was 0.77 [8].…”
Section: Discussionmentioning
confidence: 76%
“…Risk factors for unfavorable outcomes in our own study and in other studies have consistently included high viral load and low CD4 counts at baseline, having a history of being lost to follow-up and experiencing delayed switching to second-line ART after first-line failure [2,7,8,13,25]. Although there were small numbers of patients who were injection drug users in our study, they have a higher risk of developing unfavorable outcomes similar to what has been shown elsewhere [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, we used this failure rate to maintain a conservative modelling approach. Patients confirmed to have virologically failed first‐line therapy and have had a one‐time opportunity for re‐suppression were then switched to a subsequent and last PI‐based ART regimen of atazanavir (ATV)/ritonavir/TDF/3TC .…”
Section: Methodsmentioning
confidence: 99%
“…The pill count showed that the majority of patients (94%, 95% CI: 89-97) on second line ART were adherent to the treatment with more than 95% compliance. In another study [7]interestingly, 17/50 (34.0 %) of patients who had ongoing viremia or virological failure at 6 months adequately suppressed their viral load at 12 months. Another Similar findings were observed in a study where 62 % patients suspected of second-line ART failure, responded to enhanced adherence support and had a two-log decrease in their level of HIV on subsequent VL testing [8].…”
Section: Discussionmentioning
confidence: 93%